The activity of Lodz Branch of Social Committee against Tuberculosis and Lung Diseases from 1972 to 2003 - Miśkiewicz, Marta (Polish Journal of Public Health, 2011)
The Social Committee against Tuberculosis in Lodz was founded in 1958 as one of 18 social organizations with common goal to fight tuberculosis. After the Central Board in Warsaw was established in 1972, the Committee of Lodz became one of many branches of Social Committee gainst Tuberculosis and Lung Diseases. What remained was the same premises, guidelines and members with experience of many years in running educational campaigns. The Branch in Lodz cooperated with organs of government, health care and educational institutions and social organizations. The Committee organized lectures, talks, exhibitions and film projections; it broadcasted radio-plays and announcements. The Committee gave away thousands of promotional materials. The organization was especially active during first ten days of December during the “Anti-tuberculosis Days”. Despite the organizational, financial and personnel difficulties in the 90-ties of 20th century – the Committee in Lodz worked for three full decades up to 2003.